Mechanisms of sepsis-induced acute liver injury: a comprehensive review - Guo, Yongjing; Guo, Wanxu; Chen, Huimin; Sun, Jian; Yin, Yongjie (Frontiers in Cellular and Infection Microbiology, 2025)
Sepsis is a severe, often life-threatening form of organ dysfunction that arises from an inappropriately regulated host response to infectious pathogen exposure. As the largest gland in the body, the liver serves as a regulatory hub for metabolic, immune, and detoxification activity. It is also an early sepsis target organ such that hepatic dysfunction is observed in 34-46% of patients with sepsis. The precise mechanisms that give rise to sepsis-induced liver injury, however, remain incompletely understood. Based on the research conducted to date, dysregulated systemic inflammation, microbial translocation, microcirculatory abnormalities, cell death, metabolic dysfunction, and liver inflammation may all contribute to the liver damage that can arise in the context of septicemia. This review was developed to provide an overview summarizing the potential mechanisms underlying sepsis-induced liver injury, informing the selection of potential targets for therapeutic intervention and providing a framework for the alleviation of patient symptoms and the improvement of prognostic outcomes.